Magneto-actuated immunoassay for the detection of Mycobacterium fortuitum in hemodialysis water - Brugnera, Michelle Fernanda [UNESP]; Bundalian, Reynaldo; Laube, Tamara; Julián, Esther; Luquin, Marina; Zanoni, Maria Valnice Boldrin [UNESP]; Pividori, Maria Isabel (Elsevier, 2016)
This paper addresses a sensitive method for the detection of mycobacteria in hemodialysis water samples based on a magneto-actuated immunoassay with optical readout. In this approach, micro (2.8 μm) sized magnetic particles were modified with an antibody against the lipoarabinomannan (LAM) located in the mycobacterial cell wall. The system relies on the immunocapturing of the mycobacteria with the tailored antiLAM magnetic particles to pre-concentrate the bacteria from the hemodialysis samples throughout an immunological reaction. The performance of the immunomagnetic separation on the magnetic carrier was evaluated using confocal microscopy to study the binding pattern, as well as a magneto-actuated immunoassay with optical readout for the rapid detection of the bacteria in spiked hemodialysis samples. In this approach, the antiLAM polyclonal antibody was labeled with fluorescein isothiocyanate. The optical readout was achieved by the incubation with a secondary anti-fluorescein antibody labeled with peroxidase as optical reporter. The magneto-actuated immunoassay was able to detect mycobacteria contamination in hemodialysis water at a limit of detection of 13 CFU mL-1 in a total assay time of 3 h without any previous culturing pre-enrichment step.
Keywords: Hemodialysis water; Immunomagnetic separation; Magneto-actuated immunoassay; Mycobacterium fortuitum